The Health protection measures of dental practitioners implications for dental education - Huerto, Anna Kristin C. (The Journal of the Philippine Dental Association)
The study assessed the health protection measures practiced by dental practitioners in their dental clinics in accordance with the Occupational Safety and Health Administration (OSHA) guidelines and the extent the protection measures were being implemented in relation to its mode of transmission: blood borne, airborne, water borne and direct contract. The study included forty-three (43) dental practitioners with an age range of 24-41 years and 17 years of practice. In order to achieve optimum health protection, infection control procedures can never be far behind.